Prediction the wear of sliding bearings - Aleksandr, Dykha; Dmitry, Marchenko (International Journal of Engineering and Technology, 2018)
The problem of developing a calculation-experimental method for calculating wear of a sliding bearing based on a two-factor wear model (contact pressure - sliding velocity) with identification of wear resistance parameters was considered. On the basis of the proposed wear model, the wear-contact problem for a cylindrical sliding bearing was solved. The equation of equilibrium for medium pressures and the approximating function of linear wear from the arc of contact between the shaft and the bushing were used as the determining equations. To identify parameters of wear resistance in the wear model, a calculation-experimental method for determining calculated dependences of wear resistance parameters was developed on the basis of the wear test by the Â«cone â€“ three ballsÂ» scheme. The results of wear tests of bronze conical specimens with a variable wear spot and two values of sliding velocity were taken as a base. The obtained results were recommended for predicting wear of sliding bearings at the design stage and optimizing their design and operational parameters.Â Â